Pollution-Induced Food Safety Problem in China: Trends and Policies - Li, Qianhui; Zhu, Kunyang; Liu, Lei; Sun, Xinyi (Frontiers in Nutrition, 2021)
Based on systematic literature study and policy document analysis, this paper investigates the environmental pollution-induced food safety problem in China, including the impact of environmental pollution on food safety and the policy response of Chinese government since 1970s. The results show that, to different degrees, China’s food safety is affected by large but inefficient chemical fertilizer and pesticides residue (although the consumption began to decline after around 2015), cropland heavy metal pollution (especially cadmium), water pollution, and high ozone concentration. The evolution of China’s pollution-induced food safety policies can be divided into four stages, i.e., preparation stage (1974-1994), construction stage (1995-2005), elaboration stage (2006-2013) and intensification stage (2014- ). Through the four stages, the increasingly stringent policy system has been featured by “from supply-safety balance to safety first”, “from multi-agency management to integrated management”, and “from ex post supervision to ex ante risk control”. To further prevent pollution and control food quality, more collaborations between the agricultural and environmental agencies and more specific policies should be anticipated.